THE ORGANIZATION OF PEDAGOGICAL SUPPORT OF FUTURE TEACHER’S PROFESSIONAL DEVELOPMENT IN GREAT BRITAIN - Palaguta, Ilona (Studies in Comparative Education, 2017)
In the article the basic problems of the pedagogical support of future teacher’s professional development in Great Britain are analyzed. Basic approaches to the determination of the concept «pedagogical support» are presented, pedagogical support described as a special sphere of the pedagogical activity, directed to help in development and assistance of future teacher’s self-determination, decision their individual problems, related to help in studies, developing a requirement in progress of independent actions; systematic, purposeful activity of teacher, which provides opening of future teacher’s potential by the concrete help in the independent overcoming of difficulties in studies and assistance in self-determination in the future teacher’s realization. The «period of young teacher’s entrance on his position” is reflected and described, which was developed in an order to provide all young specialists support during the first-year of work at school. It combines the program of the personal development, support and professional dialogue, with monitoring and evaluation of activity in accordance with professional standards. Tasks, which a young specialist must execute to become the professional are marked: has the individual program of the planned professional development; has a tutor, with whom he plans his professional development, and who helps and supports in all spheres of activity; has attendance of engaging a tutor or other experimental colleagues. The «type of a young specialist», the beginning and development of his career is presented. It was developed with the purpose to help a young specialist to think about his professional development from principal items in relation to the adaptation period and his result. With the help of the «type of a young specialist», a young teacher puts aims, tasks, plans and the row of possibilities of his professional growth together with the tutor. 3 basic stages of young specialist’s adaptation are presented and reflected. The value of the organization of the pedagogical support is generalized, and also tasks which are put by a specialist to a future teacher in relation to his professional becoming.